ANALISIS DAMPAK PENGEMBANGAN BANDAR UDARA WAMENA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN JAYAWIJAYA - obatius wanimbo; Risky Novan Ngutra; Apolo Safanpo (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
The development of Wamena airport transportation infrastructure is able to encourage new growth centers that have an impact on economic growth for the surrounding area. Along with the increasing number of visitors and airport passengers, the existing service facilities around the airport will be needed, so that the airport will foster trade and service activities that are able to provide jobs for the surrounding community. The most visible impact of the existence of a new airport in an area is the shift of business activity units and changes in land use carried out by the community around the airport. With the impact of the construction of the airport after it was developed. The community is manifested in the form of perceptions from the public regarding the airport development plan as well as the tendency for business reorientation plans to be carried out after the airport is built. Perceptions related to business reorientation are needed because in the end they will find out which business directions are in demand by the community around the airport affected area due to changes in land function on economic growth by affecting the surrounding economic growth.